Spatiotemporal Variation and Influencing Factors of Water Yield in Drinking Water Sources - Liu Anyou; Zou Jin; Liu Lei; Zhou Qibin; Li Yang; Rong Yi; He Xiao (Shuitu baochi tongbao, 2023)
[Objective] The spatial and temporal distribution of water yield at Yunlong Reservoir basin (one of the sources of drinking water in Kunming) from 2001 to 2020 was studied in order to provide a scientific basis for the sustainable development of a water yield service function, and for constructing an ecological compensation mechanism and ecological protection policies. [Methods] We used the InVEST model and the ArcGIS spatial geographic analysis tool to determine the spatial and temporal changes of water yield. The factors influencing these changes were compared and analyzed by multi-scenario analysis and the difference comparison method. [Results] ① The water yield of Yunlong Reservoir basin showed seasonal distribution characteristics, mostly concentrated in summer. From 2001 to 2020, the water yield of Yunlong Reservoir basin initially decreased and then increased. The average water yield per unit area in the three study phases were 495 mm, 278 mm, and 364 mm, respectively. ② Water production gradually increased spatially from southwest to northeast, with high values located in the northeast and low values in the middle. ③ The contribution rates of land use change, precipitation, and potential evapotranspiration to water yield change at Yunlong Reservoir basin from 2001 to 2020 were 1.93%, 85.66%, and 12.41%, respectively. [Conclusion] Climate was the dominant factor affecting water yield changes at Yunlong Reservoir basin, and changes in land use type had the smallest impact on water yield. The annual water yield of forest land was the highest among the land use types. In the future, efforts should be made at Yunlong Reservoir basin to reduce the waste heat released to the atmosphere by human production activities and life, to strengthen the construction and protection of water conservation forests, and to reduce the negative impacts of human activities on climate which are the results of changing the underlying surface properties.